Preliminary evaluation of a novel group-based motivational interviewing intervention with adolescents: a feasibility study - Vallentin-Holbech, Lotte; Karsberg, Sidsel Helena; Nielsen, Anette Søgaard; Feldstein Ewing, Sarah W.; Rømer Thomsen, Kristine (Frontiers in Public Health, 2024)
Drinking is closely intertwined with social life among many adolescents, particularly in Europe. Group-based interventions, such as group-based motivational interviewing (group MI), have shown the capacity to prevent and reduce hazardous drinking and related problems among adolescents, but few examinations have been conducted in a European high school setting. This study examines the preliminary outcomes of a pilot group MI intervention among Danish adolescents.High school students (ages 15-18 years) were randomly allocated to two 1-hour group MI sessions delivered in a school setting (N=65) or an assessment only control condition (N=67).Data were collected in August and November 2020 using online self-administrated questionnaires regarding the acceptability of the intervention and hazardous alcohol use.The pilot group MI intervention showed high feasibility and acceptability in this setting and with this age group. Group MI adolescents significantly reduced peak drinks per drinking day compared to assessment only adolescents (-2.7 drinks, p<0.05). Results are discussed in relation to the metrics being evaluated during COVID-19 lockdown, including increased social restrictions at follow-up compared to baseline.Group MI shows promise for reducing hazardous alcohol use among Danish adolescents. In addition, the findings indicate the importance of building on and extending this work in future larger, better-powered randomized controlled trials.